High-performance concrete and preparation method thereof
By using silane-modified ZIF-8@magnesium aluminum hydrotalc and PVA fibers in high-performance concrete, the problem of insufficient improvement of compressive strength and flexural strength in the prior art is solved, and significant mechanical performance improvement is achieved. Excellent market prospects.
Patent Information
- Application Number
- CN202411245701.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-performance concrete is not effective enough in improving compressive strength and flexural strength, and cannot meet the needs of the development of the times.
The silane-modified ZIF-8@magnesium aluminum hydrotalcite is used to combine with PVA fibers to improve the mechanical properties of concrete by optimizing raw material ratio and preparation method. The specific steps include loading magnesium-aluminum hydrotalcite on the surface of ZIF-8, and modifying it with silane coupling agent, combining PVA fibers and dispersants, promoting the dispersion and hydration of concrete and improving the internal microstructure.
It significantly improves the compressive strength and flexural strength of concrete, improves mechanical properties, and has excellent market prospects.
Smart Images

Figure BDA0005030644670000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete, and more specifically, relates to a high performance concrete and a preparation method thereof. Background Art
[0002] High performance concrete (HPC) has the characteristics of high compressive strength, strong deformation resistance, low porosity, and high density, thus having better durability and workability. Therefore, it is of great significance to improve the mechanical properties of HPC. Adding various fiber reinforcement materials to concrete is the main means to improve the mechanical properties and durability of concrete.
[0003] MOFs have the characteristics of large specific surface area, easy modification, and good water stability. Moreover, adding MOFs to concrete is conducive to regulating the formation of regular microstructures of cement-based materials, thereby improving the mechanical properties of concrete.
[0004] CN118184273A discloses a crack-resistant ultra-high performance concrete for underground engineering in water-rich strata and its preparation method and application, belonging to the technical field of building materials. It is prepared from the following raw materials by mass: 550-650 parts of cement, 140-180 parts of fly ash, 120-150 parts of silica fume, 200-300 parts of calcined shield slag, 30-50 parts of micron-grade magnesium oxide, 30-50 parts of nano-grade magnesium oxide, 30-50 parts of rheology-modifying material, 800-1000 parts of lightweight aggregate, 4-8 parts of water reducer and 50-200 parts of water; the rheology-modifying material has a fluidity ratio of 106%. The present invention respectively adds calcined shield slag, micron / nano-grade magnesium oxide and lightweight aggregate into the ultra-high performance concrete, which can effectively inhibit the shrinkage of the ultra-high performance concrete and reduce the occurrence of cracks.
[0005] CN118084414A discloses an ultra-high performance concrete and a preparation method thereof. According to the invention, gravel, cement, cellulose sulfonate water-reducing agent, ferrocene-modified phenolic resin, epoxy resin, naphthalene-modified silicone rubber and steel fiber are added into a mixer according to a proportion, and stirred evenly to obtain the ultra-high performance concrete. During the stirring and blending process, the double bonds in the cardanol in the ferrocene-modified phenolic resin react with the silicone rubber terminal hydrogen in the naphthalene-modified silicone rubber to generate stable chemical crosslinks, which are evenly distributed in the concrete, thereby increasing the toughness of the concrete. At the same time, the ultra-high performance concrete of the invention has good anti-corrosion performance and compressive resistance.
[0006] CN118063172A discloses a silane-modified anti-penetration ultra-high performance concrete and its preparation method and application, which belongs to the technical field of new building materials. The concrete includes the following components by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of copper-plated straight steel fibers, 6-10 parts of silane, 0.2-0.6 parts of defoaming agent, and 410-510 parts of water. The present invention introduces silane into the ultra-high performance concrete matrix to modify the concrete. After silane is hydrated, it combines with CSH to form a silane-CSH covalent bond (dissociation energy is 628kJ / mol), replacing the van der Waals force (dissociation energy is 0.4-4kJ / mol), effectively improving the static mechanical properties and high-speed impact explosion resistance of traditional ultra-high performance concrete, and significantly improving the anti-penetration performance on the premise that the ultra-high performance concrete has extremely high strength.
[0007] CN118184269A discloses an alkali-resistant glass fiber ultra-high performance concrete and a preparation method thereof, belonging to the technical field of building materials. The raw materials of the alkali-resistant glass fiber ultra-high performance concrete include, by weight, 80-100 parts of silicate cement, 100-120 parts of aggregate, 90-100 parts of admixture, 200-220 parts of pure water, 10-15 parts of water reducer, and 30-50 parts of glass fiber. The present invention optimizes the raw material batching and introduces alkali-resistant glass fiber to improve the shortcomings of poor durability, weak fatigue resistance, easy corrosion, easy entanglement, and uneven dispersion of steel fiber ultra-high performance concrete and basalt fiber ultra-high performance concrete in the prior art. Improve the compressive strength, splitting resistance, flexural strength, durability and toughness of concrete materials, and reduce concrete shrinkage cracking.
[0008] High-performance concrete can improve compressive strength and flexural strength by optimizing raw material ingredients, but the improvement is not very obvious and cannot meet the needs of development of the times. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a high-performance concrete and a preparation method thereof. In parts by weight, the concrete comprises the following: 100 to 160 parts of P·O 42.5 cement, 20 to 40 parts of fly ash, 100 to 140 parts of quartz sand, 20 to 40 parts of silane-modified ZIF-8@magnesium-aluminum hydrotalcite, 15 to 25 parts of PVA fiber, 4 to 8 parts of water reducer, 4 to 6 parts of defoamer, 2 to 6 parts of dispersant, and 90 to 130 parts of water. The present invention prepares silane-modified ZIF-8@magnesium-aluminum hydrotalcite and cooperates with PVA fiber to jointly promote the significant improvement of the mechanical properties of concrete. The high-performance concrete prepared by the present invention has excellent market prospects.
[0010] The object of the present invention is to provide a high performance concrete.
[0011] Another object of the present invention is to provide a method for preparing high performance concrete.
[0012] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0013] A high performance concrete, comprising the following in parts by weight:
[0014] P·O 42.5 cement 100-160 parts;
[0015] 20-40 parts of fly ash;
[0016] 100-140 parts of quartz sand;
[0017] Silane-modified ZIF-8@magnesium-aluminum hydrotalcite 20-40 parts;
[0018] 15-25 parts of PVA fiber;
[0019] 4-8 parts of water reducing agent;
[0020] 4-6 parts of defoaming agent;
[0021] 2 to 6 parts of dispersant;
[0022] 90-130 parts of water.
[0023] In a preferred embodiment, the silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate and 3-aminopropyltrimethoxysilane, and the molar ratio of the 3-(trimethoxysilyl)propyl methacrylate to 3-aminopropyltrimethoxysilane is 1:4-6.
[0024] A further preferred technical solution is that the preparation method of the silane-modified ZIF-8@magnesium-aluminum hydrotalcite comprises the following steps:
[0025] (1) Dispersing zinc salt and 2-methylimidazole in ethanol by ultrasonication, reacting at 50-70° C. for 1-4 h, cooling to room temperature, filtering, washing, and vacuum drying at 60-80° C. to constant weight to obtain ZIF-8;
[0026] (2) dispersing the ZIF-8, magnesium salt, aluminum salt and urea obtained in step (1) into deionized water and stirring for 10 to 30 minutes; then performing a hydrothermal reaction, cooling to room temperature, filtering, washing, and vacuum drying at 60 to 80° C. to constant weight to obtain ZIF-8@magnesium aluminum hydrotalcite;
[0027] (3) The ZIF-8@Mg-Al-hydrotalcite obtained in step (2) and the silane coupling agent are ultrasonically dispersed in ethanol water, and then stirred at 50-70° C. for 2-6 h, filtered, washed, and vacuum dried at 60-80° C. to constant weight to obtain silane-modified ZIF-8@Mg-Al-hydrotalcite.
[0028] Preferably, in step (1), the molar ratio of the zinc salt to 2-methylimidazole is 1:4-12; and the zinc salt is at least one of zinc nitrate, zinc chloride and zinc acetate.
[0029] Preferably, in step (2), the magnesium salt is at least one of magnesium nitrate, magnesium chloride, and magnesium acetate; the aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum acetate; and the ratio of ZIF-8, magnesium salt, aluminum salt, and urea is 100 g: 0.5 mol; 0.5-1.5 mol: 12-14 mol.
[0030] Preferably, in step (3), the volume ratio of ethanol to water is 3:1; and the mass ratio of ZIF-8@magnesium aluminum hydrotalcite to silane coupling agent is 100:4-8.
[0031] Preferably, in step (3), the silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate and 3-aminopropyltrimethoxysilane, and the molar ratio of 3-(trimethoxysilyl)propyl methacrylate to 3-aminopropyltrimethoxysilane is 1:4-6; and the hydrothermal condition is a hydrothermal reaction at 110-130° C. for 4-8 hours.
[0032] In a preferred embodiment, the particle size of the fly ash is 20-60 μm; the particle size of the quartz sand is 100-200 μm; the length of the PVA fiber is 10-20 mm, and the aspect ratio is 200-400:1;
[0033] In a preferred embodiment, the water reducer is a PC-1007 polycarboxylic acid water reducer; the defoamer is an AFE-1410 defoamer; and the dispersant is hydroxyethyl cellulose.
[0034] Based on the above-mentioned method for preparing a high performance concrete, the preparation method comprises the following steps:
[0035] Silane-modified ZIF-8@Mg-Al hydrotalcite, PVA fiber and dispersant were dispersed in water and stirred at 400-600 rpm for 10-30 min, then P·O 42.5 cement, fly ash, quartz sand, water reducer and defoamer were added and stirred for 10-30 min to obtain ultra-high performance concrete.
[0036] The present invention has the following beneficial effects:
[0037] The present invention loads magnesium aluminum hydrotalcite on the surface of ZIF-8, then uses 3-(trimethoxysilyl) propyl methacrylate and 3-aminopropyl trimethoxysilane for composite modification, and uses silane coupling agents of different molecular weights to cooperate with each other, thereby promoting the dispersion of ZIF-8@magnesium aluminum hydrotalcite, improving the hydration degree and internal microstructure, promoting the improvement of concrete mechanical properties, and further improving the concrete mechanical properties by cooperating with PVA fibers and dispersants. The high-performance concrete prepared by the present invention has excellent market prospects. DETAILED DESCRIPTION
[0038] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0039] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0040] Example 1
[0041] A high performance concrete, comprising the following in parts by weight:
[0042] P·O 42.5 cement 140 parts;
[0043] 30 parts of fly ash; the particle size of the fly ash is 40 μm;
[0044] 120 parts of quartz sand; the particle size of the quartz sand is 150 μm;
[0045] 30 parts of silane-modified ZIF-8@magnesium aluminum hydrotalcite; the silane coupling agent is 3-(trimethoxysilyl) propyl methacrylate and 3-aminopropyl trimethoxysilane, and the molar ratio of 3-(trimethoxysilyl) propyl methacrylate to 3-aminopropyl trimethoxysilane is 1:5;
[0046] 20 parts of PVA fiber; the length of the PVA fiber is 15 mm, and the aspect ratio is 300:1;
[0047] 6 parts of water reducer; the water reducer is PC-1007 polycarboxylic acid water reducer;
[0048] 5 parts of defoamer; the defoamer is AFE-1410 defoamer;
[0049] 4 parts of dispersant; the dispersant is hydroxyethyl cellulose;
[0050] 110 parts water;
[0051] The preparation method of silane-modified ZIF-8@magnesium aluminum hydrotalcite comprises the following steps:
[0052] (1) 1 mol zinc nitrate and 8 mol 2-methylimidazole were ultrasonically dispersed in 200 mL ethanol, then reacted at 60° C. for 2 h, cooled to room temperature, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain ZIF-8;
[0053] (2) Dispersing 100 g of ZIF-8 obtained in step (1), 0.5 mol of magnesium nitrate, 1 mol of aluminum chloride and 13 mol of urea into 250 mL of deionized water, stirring for 20 min; then hydrothermally reacting at 120 ° C for 6 h, cooling to room temperature, filtering, washing, and vacuum drying at 70 ° C to constant weight to obtain ZIF-8@magnesium aluminum hydrotalcite;
[0054] (3) 100 g of the ZIF-8@Mg-Al-Hydrotalcite obtained in step (2) and 6 g of a silane coupling agent were ultrasonically dispersed in 200 mL of ethanol water (wherein the volume ratio of ethanol to water was 3:1), and then stirred at 60° C. for 4 h, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain silane-modified ZIF-8@Mg-Al-Hydrotalcite.
[0055] The method for preparing the high performance concrete comprises the following steps:
[0056] Silane-modified ZIF-8@Mg-Al-hydrotalcite, PVA fiber and dispersant were dispersed in water and stirred at 500 rpm for 20 min, then P·O 42.5 cement, fly ash, quartz sand, water reducer and defoamer were added and stirred for another 20 min to obtain ultra-high performance concrete.
[0057] Example 2
[0058] A high performance concrete, comprising the following in parts by weight:
[0059] P·O 42.5 cement 160 parts;
[0060] 20 parts of fly ash; the particle size of the fly ash is 20 μm;
[0061] 140 parts of quartz sand; the particle size of the quartz sand is 200 μm;
[0062] 20 parts of silane-modified ZIF-8@magnesium aluminum hydrotalcite; the silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate and 3-aminopropyltrimethoxysilane, and the molar ratio of 3-(trimethoxysilyl)propyl methacrylate to 3-aminopropyltrimethoxysilane is 1:6;
[0063] 25 parts of PVA fiber; the length of the PVA fiber is 20 mm, and the aspect ratio is 400:1;
[0064] 4 parts of water reducing agent; the water reducing agent is PC-1007 polycarboxylic acid water reducing agent;
[0065] 6 parts of defoamer; the defoamer is AFE-1410 defoamer;
[0066] 2 parts of dispersant; the dispersant is hydroxyethyl cellulose;
[0067] 130 parts water;
[0068] The preparation method of silane-modified ZIF-8@magnesium aluminum hydrotalcite comprises the following steps:
[0069] (1) 1 mol zinc chloride and 12 mol 2-methylimidazole were ultrasonically dispersed in 200 mL ethanol, then reacted at 70° C. for 1 h, cooled to room temperature, filtered, washed, and vacuum dried at 80° C. to constant weight to obtain ZIF-8;
[0070] (2) Dispersing 100 g of ZIF-8 obtained in step (1), 0.5 mol of magnesium chloride, 1.5 mol of aluminum acetate and 14 mol of urea into 250 mL of deionized water, stirring for 30 min; then hydrothermally reacting at 130 ° C for 4 h, cooling to room temperature, filtering, washing, and vacuum drying at 80 ° C to constant weight to obtain ZIF-8@magnesium aluminum hydrotalcite;
[0071] (3) 100 g of the ZIF-8@Mg-Al-Hydrotalcite obtained in step (2) and 8 g of a silane coupling agent were ultrasonically dispersed in 200 mL of ethanol water (wherein the volume ratio of ethanol to water was 3:1), and then stirred at 70° C. for 2 h, filtered, washed, and vacuum dried at 80° C. to constant weight to obtain silane-modified ZIF-8@Mg-Al-Hydrotalcite.
[0072] The preparation method of the high performance concrete is the same as that in Example 1.
[0073] Example 3
[0074] A high performance concrete, comprising the following in parts by weight:
[0075] P·O 42.5 cement 100 parts;
[0076] 40 parts of fly ash; the particle size of the fly ash is 60 μm;
[0077] 100 parts of quartz sand; the particle size of the quartz sand is 100 μm;
[0078] 40 parts of silane-modified ZIF-8@magnesium aluminum hydrotalcite; the silane coupling agent is 3-(trimethoxysilyl) propyl methacrylate and 3-aminopropyl trimethoxysilane, and the molar ratio of 3-(trimethoxysilyl) propyl methacrylate to 3-aminopropyl trimethoxysilane is 1:4;
[0079] 15 parts of PVA fiber; the length of the PVA fiber is 10 mm, and the aspect ratio is 200:1;
[0080] 8 parts of water reducing agent; the water reducing agent is PC-1007 polycarboxylic acid water reducing agent;
[0081] 4 parts of defoaming agent; the defoaming agent is AFE-1410 defoaming agent.
[0082] 6 parts of dispersant; the dispersant is hydroxyethyl cellulose;
[0083] 90 parts of water;
[0084] The preparation method of silane-modified ZIF-8@magnesium aluminum hydrotalcite comprises the following steps:
[0085] (1) 1 mol zinc acetate and 4 mol 2-methylimidazole were ultrasonically dispersed in 200 mL ethanol, then reacted at 50° C. for 4 h, cooled to room temperature, filtered, washed, and vacuum dried at 60° C. to constant weight to obtain ZIF-8;
[0086] (2) Dispersing 100 g of ZIF-8 obtained in step (1), 0.5 mol of magnesium acetate, 0.5 mol of aluminum nitrate and 12 mol of urea into 250 mL of deionized water, stirring for 10 min; then hydrothermally reacting at 110 ° C for 8 h, cooling to room temperature, filtering, washing, and vacuum drying at 60 ° C to constant weight to obtain ZIF-8@magnesium aluminum hydrotalcite;
[0087] (3) 100 g of the ZIF-8@Mg-Al-Hydrotalcite obtained in step (2) and 4 g of a silane coupling agent were ultrasonically dispersed in ethanol water (wherein the volume ratio of ethanol to water was 3:1), and then stirred at 50° C. for 6 h, filtered, washed, and vacuum dried at 60° C. to constant weight to obtain silane-modified ZIF-8@Mg-Al-Hydrotalcite.
[0088] The preparation method of the high performance concrete is the same as that in Example 1.
[0089] Comparative Example 1
[0090] Comparative Example 1 is the same as Example 1 except for the difference between the two. The difference is that the silane coupling agent is 3-aminopropyltrimethoxysilane.
[0091] Comparative Example 2
[0092] Comparative Example 2 is the same as Example 1 except for the difference between the two. The difference is that an equal amount of silane-modified magnesium-aluminum hydrotalcite is used to replace the silane-modified ZIF-8@ magnesium-aluminum hydrotalcite. The preparation method of the silane-modified magnesium-aluminum hydrotalcite comprises the following steps:
[0093] (1) 0.5 mol of magnesium nitrate, 1 mol of aluminum chloride and 13 mol of urea were dispersed in 250 mL of deionized water and stirred for 20 min; then hydrothermally reacted at 120° C. for 6 h, cooled to room temperature, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain magnesium aluminum hydrotalcite;
[0094] (3) 100 g of the magnesium aluminum hydrotalcite obtained in step (2) and 6 g of a silane coupling agent were ultrasonically dispersed in 200 mL of ethanol water (wherein the volume ratio of ethanol to water was 3:1), and then stirred at 60° C. for 4 h, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain silane-modified magnesium aluminum hydrotalcite.
[0095] Comparative Example 3
[0096] Comparative Example 3 is the same as Example 1 except for the difference between the two. The difference is that an equal amount of silane-modified ZIF-8 is used to replace the silane-modified ZIF-8@magnesium-aluminum hydrotalcite. The preparation method of the silane-modified ZIF-8 comprises the following steps:
[0097] (1) 1 mol zinc nitrate and 8 mol 2-methylimidazole were ultrasonically dispersed in 200 mL ethanol, then reacted at 60° C. for 2 h, cooled to room temperature, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain ZIF-8;
[0098] (3) 100 g of ZIF-8 obtained in step (2) and 6 g of silane coupling agent were ultrasonically dispersed in 200 mL of ethanol water (wherein the volume ratio of ethanol to water was 3:1), and then stirred at 60° C. for 4 h, filtered, washed, and vacuum dried at 70° C. to constant weight to obtain silane-modified ZIF-8.
[0099] Comparative Example 4
[0100] Comparative Example 4 is the same as Example 1 except that an equal amount of silane-modified ZIF-8@magnesium-aluminum hydrotalcite is used to replace the PVA fiber.
[0101] The mechanical properties of Examples 1-3 and Comparative Examples 1-4 were tested, and the specific test results are shown in Table 1.
[0102] Among them, according to (GB / T 50081-2019), the 7d and 28d compressive strength and 7d and 28d flexural strength of high performance concrete are measured.
[0103] Table 1:
[0104]
[0105] As can be seen from Table 1, by comparing Examples 1-3 with Comparative Examples 1-4, the high performance concrete prepared by the present invention has excellent compressive strength and flexural strength. Moreover, the silane-modified ZIF-8@ magnesium-aluminum hydrotalcite and PVA fiber prepared by the present invention jointly promote the performance improvement of high performance concrete.
[0106] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high performance concrete, characterized in that: The concrete comprises the following in parts by weight: P·O 42.5 cement 100-160 parts; 20-40 parts of fly ash; 100-140 parts of quartz sand; Silane-modified ZIF-8@magnesium-aluminum hydrotalcite 20-40 parts; 15-25 parts of PVA fiber; 4-8 parts of water reducing agent; 4-6 parts of defoaming agent; 2 to 6 parts of dispersant; 90-130 parts of water.
2. A high performance concrete according to claim 1, characterized in that: The silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate and 3-aminopropyltrimethoxysilane, and the molar ratio of the 3-(trimethoxysilyl)propyl methacrylate to the 3-aminopropyltrimethoxysilane is 1:4-6.
3. A high performance concrete according to claim 1 or 2, characterized in that: The preparation method of the silane-modified ZIF-8@magnesium-aluminum hydrotalcite comprises the following steps: (1) Dispersing zinc salt and 2-methylimidazole in ethanol by ultrasonication, reacting at 50-70° C. for 1-4 h, cooling to room temperature, filtering, washing, and vacuum drying at 60-80° C. to constant weight to obtain ZIF-8; (2) dispersing the ZIF-8, magnesium salt, aluminum salt and urea obtained in step (1) into deionized water and stirring for 10 to 30 minutes; then performing a hydrothermal reaction, cooling to room temperature, filtering, washing, and vacuum drying at 60 to 80° C. to constant weight to obtain ZIF-8@magnesium aluminum hydrotalcite; (3) The ZIF-8@Mg-Al-hydrotalcite obtained in step (2) and the silane coupling agent are ultrasonically dispersed in ethanol water, and then stirred at 50-70° C. for 2-6 h, filtered, washed, and vacuum dried at 60-80° C. to constant weight to obtain silane-modified ZIF-8@Mg-Al-hydrotalcite.
4. A high performance concrete according to claim 3, characterized in that: In step (1), the molar ratio of the zinc salt to 2-methylimidazole is 1:4-12; the zinc salt is at least one of zinc nitrate, zinc chloride and zinc acetate.
5. The high performance concrete according to claim 3, characterized in that: In step (2), the magnesium salt is at least one of magnesium nitrate, magnesium chloride, and magnesium acetate; the aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum acetate; the ratio of ZIF-8, magnesium salt, aluminum salt, and urea is 100 g: 0.5 mol; 0.5-1.5 mol: 12-14 mol.
6. The high performance concrete according to claim 3, characterized in that: In step (3), the volume ratio of ethanol to water is 3:1; the mass ratio of ZIF-8@magnesium aluminum hydrotalcite to silane coupling agent is 100:4-8.
7. The high performance concrete according to claim 3, characterized in that: In step (3), the silane coupling agent is 3-(trimethoxysilyl)propyl methacrylate and 3-aminopropyltrimethoxysilane, and the molar ratio of 3-(trimethoxysilyl)propyl methacrylate to 3-aminopropyltrimethoxysilane is 1:4-6; the hydrothermal condition is a hydrothermal reaction at 110-130° C. for 4-8 hours.
8. The high performance concrete according to claim 1, characterized in that: The particle size of the fly ash is 20-60 μm; the particle size of the quartz sand is 100-200 μm; the length of the PVA fiber is 10-20 mm, and the aspect ratio is 200-400:
1.
9. The high performance concrete according to claim 1, characterized in that: The water reducer is PC-1007 polycarboxylic acid water reducer; the defoamer is AFE-1410 defoamer; and the dispersant is hydroxyethyl cellulose.
10. A method for preparing high performance concrete according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Silane-modified ZIF-8@Mg-Al hydrotalcite, PVA fiber and dispersant were dispersed in water and stirred at 400-600 rpm for 10-30 min, then P·O 42.5 cement, fly ash, quartz sand, water reducer and defoamer were added and stirred for 10-30 min to obtain ultra-high performance concrete.
Citation Information
Cited By
Anti-cracking concrete and production process thereof
CN122010503A
Sulfate-erosion-resistant concrete and preparation method thereof
CN122254839A
